Studies of forensically important flies of Calliphoridae and Sarcophagidae in Malaysia : Morphological taxonomy, geographical and ecological distribution, species succession on carcasses, and DNA-based identification / Tan Siew Hwa - Tan, Siew Hwa (2012)
In forensic entomology, knowledge of insect taxonomy, development, behaviour and ecology is required to allow accurate data interpretation from entomological evidence in investigations. In this thesis, five forensic entomology related studies have been carried out and discussed in two Malaysian forensically important fly families, the Calliphoridae and Sarcophagidae. These studies involve the taxonomy, species checklist, ecological distribution, dipteran succession pattern on pig carcasses in Sarawak and DNA-based species identification analysis. A detailed taxonomical study of Sarcophagidae encompasses the examination of external morphological characters, and their terminology was constructed. Several important taxonomical characters were identified and their usefulness in establishing taxonomical key was evaluated. Knowledge of basic anatomy is important when inferring relationships among the sarcophagid flies. The ecological distribution study of Calliphoridae and Sarcophagidae explores whether certain species are more associated with particular ecological habitats (e.g. urban, forest, swamp, etc.). Environmental influences (e.g. habitats and elevations) are discussed with regard to the presence of fly species. Habitat-specific species were also proposed. Understanding the distribution and ecology of these fly species may facilitate criminal investigations, especially in determining the location of the first crime scene. Species checklists of Calliphoridae and Sarcophagidae were also obtained. Rates and stages of decomposition of two scavenged and clothed pig carcasses were studied in a tropical rainforest in Kuching, Sarawak, Malaysia. Comparisons between these two carcasses revealed that the scavenged carcass decomposed faster than the clothed one. Some important fly species were proposed to serve as the time (e.g. decomposition stage) and location (e.g. habitat) indicators. Diptera species were significantly different between these two pig carcasses due to differences in physical condition of the carcasses. The efficacy of DNA-based identification of forensically important fly Calliphoridae species in Malaysia was evaluated using two genetics markers, the cytochrome c oxidase subunit I and II as well as 28S ribosomal DNA. Evolution and speciation of Chrysomya defixa and Chrysomya pinguis, such as incomplete lineage sorting, introgressive hybridisation, and ancestral polymorphism were also discussed. PCR-RFLP analysis of cytochrome c oxidase subunit I was also employed to facilitate species identification of Chrysomya in Malaysia. Similar DNA-based study was conducted for Malaysian Sarcophagidae. However, only cytochrome c oxidase subunit I and II was included for the DNA barcoding analysis of 49 sarcophagid species. From the phylogeny, almost all species of Sarcophagidae were monophyletic except for Boettcherisca javanica, which provide strong evidence for proposal of new combination of genera, such as Rosellea notabilis, Pseudothyrsocnema borneensis, Bellieriomima globovesica and Bellieriomima uniseta.